The warped dark sector - Brax, Philippe; Fichet, Sylvain [UNESP]; Tanedo, Philip (Elsevier, 2019)
Five-dimensional braneworld constructions in anti-de Sitter space naturally lead to dark sector scenarios in which parts of the dark sector vanish at high 4d momentum or temperature. In the language of modified gravity, such feature implies a new mechanism for hiding light scalars, as well as the possibility of UV-completing chameleon-like effective theories. In the language of dark matter phenomenology, the high-energy behavior of the mediator sector changes dark matter observational complementarity. A multitude of signatures—including exotic ones—are present from laboratory to cosmological scales, including long-range forces with non-integer behavior, periodic signals at colliders, “soft bombs” events well-known from conformal theories, as well as a dark phase transition and a typically small amount of dark radiation.